Green curriculum, green campaigns, and financial rewards: limited impact on students’ pro-environmental awareness in higher education - Rizal, Ach. Syaiful; Ady, Sri Utami (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
Higher education plays a crucial role in shaping future generations’ environmental awareness and actions. This study examines whether common university strategies, such green curriculum, green campaigns, and financial rewards, effectively encourage students’ pro-environmental behavior. Using survey data from 124 accounting students at a private university in Surabaya, Indonesia, we applied Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationships among these variables. The findings suggest that both green curriculum and green campaigns show positive yet statistically insignificant effects on students’ pro-environmental behavior. It indicates that exposure to sustainability concepts and awareness initiatives alone do not guarantee behavioral change. In contrast, financial rewards demonstrate a strong and significant positive effect. It means that tangible incentives can effectively motivate students to adopt and maintain eco-friendly habits. These results highlight the importance of combining intrinsic and extrinsic motivators, as well as embedding sustainability values into campus culture through practical engagement and institutional support. We believe that our study contributes to the ongoing debate on sustainability education by showing that well-designed reward systems can encourage pro-environmental behavior.